The oldest record of bone diseases in Xenarthra (Mammalia) - Luna, Carlos Alberto (2019)
Fil: Luna, Carlos Alberto. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.